The Influence Of Digital Mindset, Technology Readiness, And Process Innovation On The Competitiveness Of Umkm In Bengkulu City - Agresti, Agresti; Soleh, Ahmad; Yustanti, Nirta Vera (Universitas Dehasen Bengkulu, 2025)
The purpose of this study is to determine the collective influence of digital mindset, technology readiness, and process innovation on the competitiveness of UMKM in Bengkulu City. This research method uses quantitative descriptive research. This study was conducted at MSMEs on Jalan Anggut, Bengkulu City. The sample size was 50 individuals, using purposive sampling. The data collection technique was a questionnaire. The data analysis technique used was quantitative descriptive research. The results of the study show that digital mindset influences the competitiveness of UMKM in Bengkulu City with a calculated t value of 2.716> t table 1.67866 and sig a = 0.009 <0,05, Technological readiness influences the competitiveness of UMKM in Bengkulu City with a calculated t value of 3.459> t table 1.67866 and sig a = 0.001 <0,05, Process innovation influences the competitiveness of UMKM in Bengkulu City with a calculated t value of 3.883> t table 1.67866 and sig a = 0.000 <0,05, Digital midset, technological readiness and process innovation simultaneously have a significant effect on the competitiveness of UMKM in Bengkulu City with a coefficient of determination (R2) of 75.1% and an Fcount value of 46.340> F table 2.81 with a significance value of 0.000 < 0,05.